Pengaruh Literasi Keuangan, Lingkungan Keluarga, dan Teman Sebaya Terhadap Perilaku Menabung Siswa: The Influence of Financial Literacy, Family Environment, and Peers on Students' Saving Behavior - Asnia, Erna Fuza; Aisyah, Iis; Sadiah, Ati (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
Tentu, ini adalah terjemahan yang baik dan benar untuk teks tersebut: The Influence of Financial Literacy, Family Environment, and Peers on Students' Saving Behavior Erna Fuza Asnia*, Iis Aisyah², Ati Sadiah³Economics Education Study Program, Siliwangi University, TasikmalayaCorresponding Author's Email: ernafuzaasnia@gmail.com Abstract The problem addressed in this research is the low saving behavior among students. This study aims to determine the influence of financial literacy, family environment, and peers on saving behavior. The research method used was a survey with an associative research design. The population for this study consisted of 552 tenth-grade students at SMA Negeri 1 Sindangkasih, with a sample of 232 students selected using a simple random sampling technique. Data were collected using a questionnaire and analyzed with multiple linear regression. The t-test results indicate that each independent variable has a positive and significant influence on saving behavior. The F-test proves that all three variables simultaneously have a positive and significant effect on saving behavior. Furthermore, the coefficient of determination (R Square) test yielded a value of 0.424, which means that financial literacy, family environment, and peers contribute 42.4% to saving behavior. Meanwhile, the remaining 57.6% is influenced by other factors not examined in this study. Therefore, these findings suggest that enhancing financial literacy, the family environment, and peer influence can contribute to an increase in students' saving behavior.